Ten UMP drivers fulfil volunteer responsibility - Nor Salwana, Mohammad Idris (2021)
PEKAN, 17 July 2021 - Every profession and every individSalual from various career backgrounds plays a role in combating the threat of the COVID -19 virus to ensure that the people and the country are always safe.